Natural History of Renal Neuroendocrine Neoplasms: A NET by Any Other Name? - Nguyen, Andrew H.; O’Leary, Michael P.; De Andrade, James P.; Ituarte, Philip H. G.; Kessler, Jonathan; Li, Daneng; Singh, Gagandeep; Chang, Sue (Frontiers in Endocrinology, 2021)
Renal neuroendocrine neoplasms are rare, with descriptions of cases limited to individual reports and small series. The natural history of this group of neuroendocrine neoplasms is poorly understood. In this study, we queried the Surveillance, Epidemiology and End Results (SEER) database over a four-decade period where we identified 166 cases of primary renal neuroendocrine neoplasms. We observed a 5-year overall survival of 50%. On multivariate analysis, survival was influenced by stage, histology, and if surgery was performed. We observed that patients managed by operative management had a greater frequency of localized or regional stage disease as well as a greater frequency of neuroendocrine tumor, grade 1 histology; whereas those managed non-operatively tended to have distant disease and histologies of neuroendocrine carcinoma, NOS and small cell neuroendocrine carcinoma. This is the largest description of patients with renal neuroendocrine neoplasms. Increased survival was observed in patients with earlier stage and favorable histologies.